A survey of palliative medicine education in Japan’s undergraduate medical curriculum - Yoichi Nakamura; Yusuke Takamiya; Mari Saito; Koichi Kuroko; Tatsuko Shiratsuchi; Kenzaburo Oshima; Yuko Ito; Satoshi Miyake (BMC Palliative Care, 2017)
Abstract Background This study aimed to examine the status of undergraduate palliative care education among Japanese medical students using data from a survey conducted in 2015. Methods A questionnaire was originally developed, and the survey forms were sent to universities. The study’s objectives, methods, disclosure of results, and anonymity were explained to participating universities in writing. Responses returned by the universities were considered to indicate consent to participate. Descriptive statistical methodology was employed. Results The response rate was 82.5% (66 of 80 medical faculties and colleges). Palliative care lectures were implemented in 98.5% of the institutions. Regarding lecture titles, “palliative medicine,” “palliative care,” and “terminal care” accounted for 42.4, 30.3, and 9.1% of the lectures, respectively. Teachers from the Department of Anesthesia, Palliative Care, and Psychiatry administered 51.5, 47.0, and 28.8% of lectures, respectively. Subjects of lectures included general palliative care (81.8%), pain management (87.9%), and symptom management (63.6%). Clinical clerkship on palliative care was a compulsory and non-compulsory course in 43.9 and 25.8% of the schools, respectively; 30.3% had no clinical clerkship curriculum. Conclusions Undergraduate palliative care education is implemented in many Japanese universities. Clinical clerkship combined with participation in actual medical practice should be further improved by establishing a medical education certification system in compliance with the international standards.